CDKN1B Val 109 Gly variant is not related to risk of prostate cancer. Issue 10 (30th June 2019) - Zhu, Lijie; Wang, Jun; Yue, Chuang; Yuan, Wei; Zhang, Wei; Shi, Li; Mi, Yuanyuan; Wu, Xingyu; Zhang, Li‐Feng; Zuo, Li
Abstract: Association between CDKN1B gene Val 109 Gly polymorphism and prostate cancer (PCa) susceptibility has been investigated in several studies but with inconsistent conclusions. We adopted odds ratios (ORs) and 95% confidence intervals (CIs) to assess the correlation between CDKN1B Val 109 Gly variant and PCa susceptibility. Moreover, we used in‐silico tools to evaluate the relationship of CDKN1B expression and overall survival (OS) or disease free survival (DFS) time in PCa patients. The overall results demonstrated no association of the CDKN1B variant on PCa risk [allelic contrast (OR = 0.78, 95% CI = 0.45 − 1.35, P heterogeneity  = 0.038); GV vs VV (OR = 0.83, 95% CI = 0.56 − 1.25, P heterogeneity  = 0.253); GG vs VV (OR = 0.48, 95% CI = 0.23 − 1.01, P heterogeneity  = 0.161); GG+GV vs VV (OR = 0.75, 95% CI = 0.52 −1.08, P heterogeneity  = 0.132) and GG vs GV+VV (OR = 0.63, 95% CI = 0.25 − 1.11, P heterogeneity  = 0.152)]. In subgroup analysis by ethnicity and source of control, we also identified similar results. In‐silico results showed that expression of CDKN1B was decreased in PCa tissue, especially in less advanced PCa (Gleason score = 6 or 7). No significant difference of OS or DFS time was indicated between the low and high expression of CDKN1B . Our present study showed evidence that CDKN1B Val 109 Gly variant is not related to PCa risk. Future studies with large sample size are needed to confirm this correlation in more details. Abstract : Our present study suggested that CDKN1B Val 109 Gly polymorphism may not be related to polymorphism and prostate cancer (PCa) risk. Although expression of CDKN1B was decreased in PCa tissue, especially in less advanced PCa, no significant difference of overall survival (OS) or disease free survival (DFS) time was indicated between the low and high expression of CDKN1B.